2013
DOI: 10.5897/jidi2013.0118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Beta-lactamase production and Antibiotics resistance in Staphylococcus aureus strains

Abstract: The antibiotic susceptibility profile and the association of β-lactamase production to antibiotic resistance in Staphylococcus aureus strains were analysed. The disk diffusion antibiotic susceptibility pattern was conducted on S. aureus strains cultured from clinical specimens using standard bacteriological methods. The β-lactamase production was assayed using the modified Perret's iodometric assay and data were statistically analysed. Of the 107 S. aureus isolates identified, 77 (72%) of the isolates were mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
2
1
2
Order By: Relevance
“…The production of β-lactamase observed in this study was 49.4% in both wound and nasal S. aureus strains but lower compared to previous studies in which 70-80% was reported (Akindele et al, 2010;Torimiro et al, 2013). This difference may be as a result of the collection of samples from limited specimens compared to the previous investigators who collected samples from various clinical specimens.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The production of β-lactamase observed in this study was 49.4% in both wound and nasal S. aureus strains but lower compared to previous studies in which 70-80% was reported (Akindele et al, 2010;Torimiro et al, 2013). This difference may be as a result of the collection of samples from limited specimens compared to the previous investigators who collected samples from various clinical specimens.…”
Section: Discussioncontrasting
confidence: 55%
“…observed to be over 80% has been documented (Parker & Collier, 1990;Schito, 2006;Akindele, Adedokun & Olaolu, 2010;Torimiro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MRSA is resistant to entire classes of β -lactams including cephalosporins and carbapenems and has higher risk of development of resistance to quinolones, aminoglycosides, and macrolides [912]. …”
Section: Introductionmentioning
confidence: 99%
“…A capacidade hidrolítica da betalactamase depende de alguns fatores como sua localização, cinética, quantidade e condições físico-químicas (Livermore 2000). Além disso, o uso indiscriminado de antimicrobianos gera uma pressão seletiva para o aparecimento dessa resistência (McDougal & Thornsberry 1986, Livermore 2000, Torimiro et al 2013, Dias et al 2015.…”
Section: Staphylococcus Spp Resistentes à Meticilina (Mrs)unclassified